THE NARRATOR’S VOICE OF FREEDOM IN RALPH ELLISON’S INVISIBLE MAN: A STUDY OF POSTCOLONIAL LITERATURE - Khotimatul Khusnah; Vita Vendityaningtyas (English Teaching Journal : A Journal of English Literature, Language and Education, 2016)
The purpose of this research is to describe the position of Black people as the folk who get discrimination in America and explain the Narrator’s voice as the Black people in conveying the equality between Black and White people in America that is represented in Invisible Man novel. This research uses qualitative research. The researcher needs postcolonial literature by Lois Tyson to get evidences the effects and goals of the author in creating a story. The analysis reveals that Black people include subordinate people, oppressed minority group, and lower class that always suppressed and exploited by superior people who have power. Black people try to fight against superior to show their feeling of freedom for getting the same position and equality as White by conveying their voice through protest. The conclusion shows that inferiority makes Black people who have lower position in society get oppression that cause physical and mental disturbance from superior and the Narrator tries to struggle and get confession of Black people from the domination of White in order to survive their existence in society by conveying the voice with non-violence way through speech, action and music.